Improving the communication skills of medical students ——A survey of simulated patient-based learning in Chinese medical universities - (:unkn) unknown (My University, 2022)
Background: It is useful to advance simulated patient (SP) participation in teaching to improve the communication skills of medical students, so this study aims to explore the current state of Chinese mainland SP education. Methods: A cross sectional survey was designed utilizing well defned quantitative research methods and descriptive statistics. The questionnaire sought information which elucidated the current status of SP-based education, the origin of SP-based learning, SP training, challenges of this learning strategy and future developments. Questionnaires were distributed to 79 medical colleges in mainland China, and 68 were returned. Of these, 64 constituted valid responses (81%). Results: The number of SP-based education activities in medical colleges ofering 5-year、7-year and 8-year clinical medicine programs was signifcantly higher than that in medical colleges which ofered only a single 5-year program (p<0.01). Communication skills training accounted for 73% of the content of SP-based learning activities, and was expected to rise in the future to 90%, in response to a need to improve doctor-patient relationships. Persons recruited as ‘simulated patients’ included students (21% of the total), residents (49%), medical staf (15%) and teaching staf (14%). Colleges, planning a SP-based education program, preferred teachers (80%) and students (55%) to assume ‘simulated patient’ roles. In objective structured clinical education (OSCE) scenarios, co-scoring by both SPs and teachers featured more highly in the ‘consultation’ station and ‘doctor-patient communication’ station. A number of factors were identifed as hindering future development and implementation of SP-based learning including budget restraints, SP selection and training. Conclusions: SP-based learning programs ofer clear benefts for improving the clinical education of medical students and their communication skills. The main obstacles to achieving more widespread and higher quality SP-based education are insufcient funding and the lack of standardized training and performance evaluation processes for simulated patients. Medical colleges should consider reducing the proportion of students and teachers acting as SPs,and attract more citizens to participate in SP-based learning activities. Formalised training and evaluation of SPs performance are necessary to establish a ‘standard simulated patient’ for a particular medical discipline, thus improving SP-based activities and student learning
Yurong Ge
Yuko Takeda
Keywords: Simulated patient, Medical education, Communication, Clinician -patient relationship